The Role of Curators and Liquidators In Solving Problems Insolvent Limited Liability Company - Jefri Yuliyanto Waisapi (Eduvest - Journal of Universal Studies, 2023)
This study aims to review and analyze the role of curators in insolvency in limited liability companies, as well to review and analyze the role of liquidators in the settlement of assets bankrupt limited liability companies. By using normative legal research methods, which use secondary data based on primary legal sources, secondary legal materials and tertiary legal materials, data collection through literature studies or document studies, as well qualitative analysis. The results showed that the curator's decision in bankruptcy in limited liability company begins in the process of managing and settling bankruptcy assets, starting from the stage management, appointment and appointment qualified curators, settlement bankruptcy assets by the curator, so that from the date bankruptcy statement decision, all executors of the management and settlement of bankruptcy assets are handed over to the curator. After Limited Liability is declared bankrupt, the task of the curator in clearing the assets in Limited Liability is to block assets of a Limited Liability Company. That the role of the liquidator in the settlement assets of a bankrupt limited liability company is that the liquidator has a position in the settlement of the assets of the dissolved company, so that it has the rights, obligations and responsibilities of the liquidator in the settlement of the assets the dissolved limited liability company, the liquidator has responsibility if the liquidation has not ended. The liquidator has a great responsibility from the time dissolution Limited Liability Company to Limited Liability Company legal entity status Limited Liability Company ends